MODEL KONSELING KELOMPOK UNTUK ANAK DENGAN GANGGUAN PEMUSATAN PERHATIAN DISERTAI HIPERAKTIVITAS (GPPH) - Romadona, Nur Fauziah (Universitas Pendidikan Indonesia, 2011)
Abstract, The core Symptoms of Attention Deficit/hyperactivity disorder (ADHD) are hyperactivity, impulsivity, and inattention, that have impact to behavior problems, academic working social, emotional and self system. Most of the diagnosis of ADHD will retain into adulthood, and has had a longlife impact to adults with ADHD. The number of children wwith ADHD in the world and particularly in Indonesia continues to increase. Current best practice guidleines advocate a multidisciplinary approach to the management of ADHD. One of the psychoeducational approach is group counseling for school based intervention that can be provided y school coounselor. Issues of self-esteem and academic/social relationships are often successfully dealt with in counseling. There are three group counseling models that can be proposed as counseling intervention in the school setting, that are Rational Emotive Behavior Therapy, Cognitive Behavior Therapy, and adventure Based Counseling/Adlerian Play TherapyKeyword: Counseling group; children; GPPH